Pharmaceutical company payments to dermatology Clinical Practice Guideline authors in Japan - Murayama, Anju (PLoS One, 2020)
Clinical Practice Guidelines (CPGs) play significant roles in most medical fields. However, little is known about the extent of financial Conflicts of Interest (FCOIs) related to pharmaceutical companies (Pharma) selling dermatology prescription products and dermatology CPG authors in Japan. The aims of this study were to elucidate the characteristics and distribution of payments from Pharma to dermatology CPG authors in Japan, and to evaluate the extent of transparency and accuracy in their FCOI disclosures. We analyzed the records of 296 authors from 32 dermatology CPGs published by the Japanese Dermatological Association from the beginning of 2015 to the end of 2018. Using the payment data reported by 79 Pharma between 2016–2017 in Japan, we investigated the characteristics of the CPG authors and the payments from the Pharma to them. Furthermore, we evaluated the transparency and accuracy of the FCOI disclosures of the individual CPG authors. Of the 296 CPGs authors, 269 authors (90.6%) received at least one payment from the Pharma. The total monetary value of payments for the 2-year period was $7,128,762. The median and mean monetary value of payments from the Pharma reporting were $10,281 (interquartile range $2,796 -$34,962) and $26,600 (standard deviation $40,950) for the two years combined. Of the 26 CPG authors who disclosed FCOIs due to the monies received from Pharma, only the atopic dermatitis CPG authors and the acne vulgaris CPG authors published their potential FCOIs. In Japan, most dermatology CPG authors received financial payments from Pharma. The transparency of the CPGs, as reported by the CPG authors, was inadequate, and a more rigorous framework of reporting and monitoring FCOI disclosure is required to improve the accuracy and transparency with relation to possible Conflicts of Interest.